Efektivitas Penerapan E-Court dalam Menyelesaikan Perkara di Pengadilan dalam Perspektif Asas Peradilan Cepat, Sederhana dan Biaya Ringan - Moh Sya'roni; Zaini Zaini; Mohammad Nurul Huda (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Digital transformation in the judicial system represents a strategic step to improve the quality of legal services in Indonesia. One of the innovations implemented by the Supreme Court of the Republic of Indonesia is the E-Court system, which enables case administration and court proceedings to be conducted electronically. This study aims to analyze the effectiveness of the implementation of E-Court in realizing the principles of simple, fast, and low-cost justice, as well as to identify the obstacles faced by parties who do not utilize the system. The research method employed is a normative legal approach, involving the analysis of statutory regulations and scholarly literature. The results indicate that, normatively, E-Court has been effective in supporting judicial efficiency; however, in practice, it still encounters various challenges, including technical, social, and institutional aspects. These obstacles vary among different legal subjects, namely advocates, individuals, private legal entities, and government legal entities. Therefore, comprehensive efforts are required to optimize the implementation of E-Court to ensure that the objectives of judicial reform can be fully achieved. Furthermore, the findings reveal that, from a normative perspective, E-Court provides a more efficient mechanism compared to conventional systems, particularly in terms of case administration and communication between parties. However, this effectiveness has not been evenly realized due to constraints such as the digital divide, limited technological infrastructure, and low user readiness. Consequently, the implementation of E-Court still requires reinforcement in both technical and cultural aspects to ensure optimal accessibility for all segments of society.